2016
DOI: 10.1111/myc.12528
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, type and treatment of fungal pathogens in toenail onychomycosis in the central Alpine region of South Tyrol, northern Italy – a 10‐year retrospective study from 2004 to 2013

Abstract: Onychomycosis is one of the most common dermatological diseases, primarily caused by dermatophytes, and sometimes, also by yeast and moulds. This study aims to clarify the frequency of isolated pathogens from mycotic toenails in the reference centre of the central Alpine mountain region of South Tyrol, northern Italy. Age and gender differences, types of pathogens and initial therapy used were also investigated. This is a retrospective study from 2004 to 2013 on the files of all patients with suspected onychom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In the present study, there was more female than male patients (60% versus 40%). Similar results were found by previous studies [7,9,27,28]. The difference might result from daily habits such as nail cosmetics, frequent water contact, detergents, raw food, cleaning materials, hydrocarbons, and trauma.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, there was more female than male patients (60% versus 40%). Similar results were found by previous studies [7,9,27,28]. The difference might result from daily habits such as nail cosmetics, frequent water contact, detergents, raw food, cleaning materials, hydrocarbons, and trauma.…”
Section: Discussionsupporting
confidence: 90%
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…interdigitale (Faergemann and Baran, 2003). The non-dermatophyte molds, such as Fusarium spp., Acremonium spp., Alternaria spp., Scopulariopsis brevicaulis, Aspergillus spp., can also be involved in the pathogenesis with estimated 10% prevalence worldwide (Gupta and Nakrieko, 2014; Gasser et al, 2016; Gupta et al, 2016; Motamedi et al, 2016). Yeasts, like Candida albicans and Candida parapsilosis , represent the third cause of nail fungal infection, but only occurring when predisposing factors are present, mainly immunosuppression, and diabetes (Arrua et al, 2015; Gasser et al, 2016).…”
Section: Discussionmentioning
confidence: 99%